Institutional And Non-Institutional Deliveries In Some Slum Areas Of Delhi : Factor Analysis - Gupta R. K (Wolters Kluwer Medknow Publications, 1999)
Research questions: What are the factors, which determine preference for institutional and non-institutional deliveries in slum area of Delhi? Objective: To study the factors determining preference for institutional or non-institutional deliveries in slum areas of Delhi. Study design: Cross-sectional. Settings: Slum areas of Delhi. Sampling: Ten slum colonies were randomly selected from Delhi by dividing it into five zones and taking two colonies from each zone. Four Hundred households were covered from each colony and information on delivery related aspects were collected from mothers of children up to 2 years of age. Statistical analysis: PC based factor analysis technique was applied to identify factors had also simple tables were generated. Results: Non-institutional deliveries were found to be about 46%. Factor such as â€˜Economic Statusâ€ was identified as determining one for preference of non-institutional deliveries. Conclusion: Improvement in economic conditions of people may promote institutional deliveries.